Model Proses Bisnis ERP, Pengendalian Manajemen dan Keunggulan Kompetitif - Muhammad Nawawi; Dabella Yunia (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2021)
This study aims to provide empirical evidence about the ERP business process model of competitive advantage. In particular, this study investigates the mediating effect of management control on the relationship between ERP implementation and competitive advantage.The empirical analysis in this study is based on primary data obtained from a survey of managers of 50 manufacturing companies with a response rate of 33.67%.This research was conducted with a structural equation modeling (SEM) approach method with testing tools using partial least squares (PLS).Directly, these findings suggest ERP implementation has a positive impact on a firm's competitive advantage, by increasing innovation opportunities that involve building greater capacity that creates long-term benefit opportunities and sustainable competitive advantage.The use of informal controls tends to be more integrated with information systems in producing higher quality information to support decision making so as to mediate the positive effect of ERP implementation in increasing the company's competitive advantage.Meanwhile, formal control cannot be a good mediator when it is not accompanied by the addition of other business attributes.